Degradation and Subsequent Regeneration of Forestry Biomass using Genetic Resource - Anuj Kumar; Manju Agarwal (International Journal of Mathematics And its Applications, 2017)
In present paper, a nonlinear mathematical model is proposed and analyzed to study the depletion of forestry resources by the human population and industrial pressure. It shows that density of forestry resource biomass decreases as the population and industrial pressure increases. We also observed the effect of genetic resources on the depletion of forestry biomass. The model is analyzed by using stability theory of differential equations. The numerical simulation analysis of the model confirms the analytical results.